A Review on Career Development Program and Performance Appraisal System on Employee Engagement Market - Madhyvadany, M.; Panboli, S. (International Journal of Psychosocial Rehabilitation, 2020)
In the contemporary business scenario, the primary objective of organisations is to maximize their wealth and feature among top notch organisations of the world by effectively utilising their resources viz., technology, process and importantly people. Of the above mentioned three resources, to retain the people and to develop their talent has become more challenging and complex due to paucity of people with unique and remarkable skills meeting the requirements of the organisation. Considering the popular belief that people are the assets of any organisation, it becomes imperative on the part of any organisation in creating the conducive environment for its people i.e employees, to explore, express and excel in their domain. To facilitate this, the construct of Employee Engagement has found its way into the planning and design of Human Resources policies of organisations. Though the emergence and existence of this construct of employee engagement can be traced back to late 20 the century it was not until the early 21st century it is gaining prominence and visibility. In the recent times, employee attrition rates in the industry is alarming, with service sector hitting as high as 30% and the employees are noticed to be swapping their positions perpetually leading to such higher turnover (attrition) rates. Thus retaining and engaging employee has become the need of the hour in this challenging scenario. Engaged employees accomplish assignment with dynamism and zeal. The commitment and desire in accomplishing the job in the best manner gets along with an employee whose engagement level is considerably high. An employee who feels engaged in his work, lays her/his most excellent effort through best use of time, intelligence, and vigour, over what is supposed to be considered adequate. They create brand new ideas, pervade their team members with their own action of engagement and remotely obtain prospects to work in another place. Hence this construct of employee engagement has now turned out to be the need of the hour for organisations as they desperately pursue to preserve their work-force engaged. The intent of this review paper is illuminate the construct, employee engagement and particularly with reference to the contributing factors of Career development program and Performance appraisal system leading to organisational performance. For this study, the author has used the method of reviewing articles and research works in the realm of employeeengagement. The aim of this review paper is consolidating the available literature on the taken topic. Expectantly, this editorial will benefit to any person looking for healthier appreciation of the same and in enhancing the productivity. This review paper, points out how factors like knowledge management, career development program and performance appraisal system under employee engagement are benefitting both at organisational and individual levels.